Neptunyl(VI) centred visible LMCT emission directly observable in the presence of uranyl(VI) - Woodall, Sean; Swinburne, Adam N.; Banik, Nidhu lal; Kerridge, Andrew; Pietro, Poppy Di; Adam, Christian; Kaden, Peter; Natrajan, Louise S. (Chemical communications, 2015)
Room temperature detection of neptunyl(VI) LMCT emission in a coordination compound and in the presence of uranyl(VI) is reported for the first time. Differences in the excitation profiles of the complexes enable spectral editing so either exclusively neptunyl(VI) or uranyl(VI) emission is observed or a sum of the two.
First published 16 December 2014
Gesehen am 03.07.2020